Dignity as a Fundamental Value of Social Law - Nitecki, Stanisław (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Dignity as an inherent value of a human being is the subject of interest of many sciences. This concept is anchored in the Constitution of the Republic of Poland and in acts falling within the scope of social law. It is the basis for actions taken in relation to people and families in a difficult life situation.It also determines the way of interpretation of legal norms underlying the issued decisions. Affects the scope of satisfying the needs related to living conditions. In this respect, can be distinguished the provision of shelter, clothing and footwear, as well as the level of satisfaction of food needs. A separate issue is the level of services provided in facilities that offer round-the-clock care. This concept has a special reference to the treatment of the deceased.